A Multicenter Study on von Willebrand Disease Realities in Yeungnam Region - Hyun Ju Kim; Ye Jee Shim; Jae Min Lee; Young Tak Lim; Eu Jeen Yang; Kyung Mi Park; Hee Won Chueh; Eun Sil Park; Hyo Sun Kim; Ji Kyoung Park; Eun Jin Choi; Seom Gim Kong; et al. (The Korean Society of Pediatric Hematology-Oncology, 2019)
Background : : von Willebrand disease (VWD) is one of the most common inherited bleeding disorders. However, the number of patients who register to the Korea Hemophilia Foundation (KHF) is much lower than the expected prevalence rate and only few hospitals perform tests for diagnosis autonomously. Thus, we surveyed practical realities of VWD in Yeungnam region. Methods : : Patients with VWD (N=267) who were diagnosed at eleven university hospitals from March 1995 to March 2018 were enrolled in this study. We evaluated the medical records from each hospital retrospectively. Results : : Two hundred and twenty-eight children and 39 adults met the diagnostic criteria for VWD. Seventy-eight (57.4%) patients had the blood type O. Fifty-eight patients were definite type 1 (21.7%), 151 were possible type 1 (56.6%), and the others were type 2. Abnormal laboratory findings were the most common factor for the diagnosis in children. VWF mutations were detected in 17 patients. Patients with a family history showed age of diagnosis of 9 y, which is higher than in those with no family history (6 yr), and also showed a higher rate of significant bleeding (32.1% vs. 14.2%). VWF:RCo and VWF:Ag tests were performed in-hospital at only 1 of 11 hospitals. Twelve of 267 patients were enrolled at the KHF (4.5%). Conclusion : : A high rate of out-sourcing studies may result in inaccurate diagnosis. The registration rate to the KHF is still lower than the prevalence rate. A comprehensive nationwide registration system is necessary in order to identify the actual prevalence rate and promote the diagnosis of VWD in Korea.